Frenulate siboglinids at high Arctic methane seeps and insight into high latitude frenulate distribution - Sen, Arunima; Didriksen, Alena; Hourdez, Stephane; Svenning, Mette Marianne; Rasmussen, Tine Lander (Ecology and Evolution, 2020)
Frenulate species were identified from a high Arctic methane seep area on Vestnesa Ridge, western Svalbard margin (79°N, Fram Strait) based on mitochondrial cytochrome oxidase subunit I (mtCOI). Two species were found: Oligobrachia haakonmosbiensis , and a new, distinct, and undescribed Oligobrachia species. The new species adds to the cryptic Oligobrachia species complex found at high latitude methane seeps in the north Atlantic and the Arctic. However, this species displays a curled tube morphology and light brown coloration that could serve to distinguish it from other members of the complex. A number of single tentacle individuals were recovered which were initially thought to be members of the only unitentaculate genus, Siboglinum . However, sequencing revealed them to be the new species and the single tentacle morphology, in addition to thin, colorless, and ringless tubes indicate that they are juveniles. This is the first known report of juveniles of northern Oligobrachia . Since the juveniles all appeared to be at about the same developmental stage, it is possible that reproduction is either synchronized within the species, or that despite continuous reproduction, settlement, and growth in the sediment only takes place at specific periods. The new find of the well‐known species O. haakonmosbiensis extends its range from the Norwegian Sea to high latitudes of the Arctic in the Fram Strait. We suggest bottom currents serve as the main distribution mechanism for high latitude Oligobrachia species and that water depth constitutes a major dispersal barrier. This explains the lack of overlap between the distributions of northern Oligobrachia species despite exposure to similar current regimes. Our results point toward a single speciation event within the Oligobrachia clade, and we suggest that this occurred in the late Neogene, when topographical changes occurred and exchanges between Arctic and North Atlantic water masses and subsequent thermohaline circulation intensified.